2005
DOI: 10.1177/030802260506801207
|View full text |Cite
|
Sign up to set email alerts
|

Yoga: An Ancient Occupational Therapy?

Abstract: Yoga is a complete system of occupational regulation, based on complex theories that address occupational risk factors while relating occupation directly to health and wellbeing. Although aspects of yoga have been used in Western occupational therapy settings, some of its underlying theories may have been overlooked. If validated by research, these theories may enrich occupational therapy philosophy. Yogic techniques of potential clinical use include pulse diagnosis, meditation and breath control. These are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Yoga is a holistic mind-body intervention that addresses the physical, cognitive, emotional, and social needs of the individual (Mailoo, 2005). Recently, the American Occupational Therapy Association (AOTA) (2016) has acknowledged yoga as a complementary integrative therapy (CIT) that can prepare and enhance participation and engagement in occupations.…”
Section: Background and Statement Of Problemmentioning
confidence: 99%
“…Yoga is a holistic mind-body intervention that addresses the physical, cognitive, emotional, and social needs of the individual (Mailoo, 2005). Recently, the American Occupational Therapy Association (AOTA) (2016) has acknowledged yoga as a complementary integrative therapy (CIT) that can prepare and enhance participation and engagement in occupations.…”
Section: Background and Statement Of Problemmentioning
confidence: 99%
“…Yoga is a holistic mind-body approach that addresses the physical, cognitive, emotional, and social needs of the individual (Mailoo, 2005). Recently, the American Occupational Therapy Association (AOTA) (2016) acknowledged yoga as a complementary integrative therapy (CIT) that can prepare and enhance participation and engagement in occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is the main occupational therapyrelevant ayurvedic intervention. Mailoo (2005) provided a very brief introduction to yoga but Grieve (2006) suggested that if components of yoga are used without a proper understanding of their context, their value might be significantly diminished. One could compare this to a person with no knowledge of haemo-dynamics using a sphygmomanometer on a patient and then giving advice on salt consumption.…”
Section: Introductionmentioning
confidence: 99%